2008
DOI: 10.1177/0193945907310559
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Practices Enabling Staff Nurses to Control Their Practice

Abstract: This mixed-methods study uses interviews, participant observations, and the CWEQII empowerment tool to identify structures and attributes of structures that promote control over nursing practice (CNP). Nearly 3,000 staff nurses completed the Essentials of Magnetism (EOM), an instrument that measures CNP, one of the eight staff nurse-identified essential attributes of a productive work environment. Strategic sampling is used to identify 101 high CNP-scoring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 34 publications
0
76
0
2
Order By: Relevance
“…In the Dimensions of Magnetism study [1][2][3][4][5][6] and in the psychometric studies 7,8,17 described, 20 616 staff nurses identified and described 5 types of nurse-physician relationships that prevail on almost all clinical units. In the 4 interview studies, [13][14][15][16] 721 staff nurses, 334 nurse managers, 229 physicians, 46 other health professionals, and 29 nurse and hospital administrators who were interviewed about nursephysician and interdisciplinary relationships described not only the different types of relationships but most importantly why "good" relationships were important to patient care and what organizational structures and leadership practices promoted the "best" relation-the unit or in the clinic result in the same kind of relationship. Staff nurse interviewees had this to say about the problem:…”
Section: The Problemmentioning
confidence: 99%
“…In the Dimensions of Magnetism study [1][2][3][4][5][6] and in the psychometric studies 7,8,17 described, 20 616 staff nurses identified and described 5 types of nurse-physician relationships that prevail on almost all clinical units. In the 4 interview studies, [13][14][15][16] 721 staff nurses, 334 nurse managers, 229 physicians, 46 other health professionals, and 29 nurse and hospital administrators who were interviewed about nursephysician and interdisciplinary relationships described not only the different types of relationships but most importantly why "good" relationships were important to patient care and what organizational structures and leadership practices promoted the "best" relation-the unit or in the clinic result in the same kind of relationship. Staff nurse interviewees had this to say about the problem:…”
Section: The Problemmentioning
confidence: 99%
“…Shared governance is a management model that promotes nurses' control of their practice and the environment in which they practice. It represents a radical departure from traditional management models in which nurses have little power within formal hierarchic structures (12,18,21) . That traditional model poses barriers between the professionals who conduct care and those who perform management activities in hospital organization (13) .…”
Section: Shared Governancementioning
confidence: 99%
“…Shared governance recognizes that the power of health managers must be shared with the professionals responsible for care practice, not imposed on them, which occurs in the traditional model (21) . The decision process in shared governance must be collective, and discussions are used to achieve a consensus (23)(24) .…”
Section: Shared Governancementioning
confidence: 99%
See 2 more Smart Citations